2019
DOI: 10.1186/s13046-019-1455-x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-8 promotes integrin β3 upregulation and cell invasion through PI3K/Akt pathway in hepatocellular carcinoma

Abstract: BackgroundInterleukin-8 (IL-8) plays a vital role in the invasion and metastasis of hepatocellular carcinoma (HCC), and is closely associated with poor prognosis of HCC patients. Integrin αvβ3, a member of the integrin family, has been reported to be overexpressed in cancer tissues and mediate the invasion and metastasis of HCC cells. However, the relationship between IL-8 and integrin αvβ3 in HCC and the underlying mechanism of IL-8 and integrin αvβ3 in the invasion of HCC remains unclear.MethodsThe expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 26 publications
1
71
0
Order By: Relevance
“… 45 , 46 Interestingly, CXCR2 also affects tumor development by mediating PI3K/AKT signaling. 47 Here, our data revealed that miR-495-3p inhibited phosphorylated level of PI3K/Akt, while overexpressing circ_0000215 promoted the PI3K/Akt activation, which was consistent with CXCR2 expression, suggesting that circ_0000215/miR-495-3p could promote glioma progression via activating PI3K/Akt through CXCR2.…”
Section: Discussionsupporting
confidence: 76%
“… 45 , 46 Interestingly, CXCR2 also affects tumor development by mediating PI3K/AKT signaling. 47 Here, our data revealed that miR-495-3p inhibited phosphorylated level of PI3K/Akt, while overexpressing circ_0000215 promoted the PI3K/Akt activation, which was consistent with CXCR2 expression, suggesting that circ_0000215/miR-495-3p could promote glioma progression via activating PI3K/Akt through CXCR2.…”
Section: Discussionsupporting
confidence: 76%
“…The RIG-I-like receptor and Toll-like receptor signaling pathways were identified in phase II, and are associated with pattern-recognition receptors (91). In addition, several pathways, including 'focal adhesion', 'Rap1 signaling pathway', 'Ras signaling pathway', 'PI3K-Akt signaling pathway' and 'Proteoglycans in cancer' were associated with invasion and metastasis (92)(93)(94)(95)(96). The two common cancer-associated signaling pathways 'Pathways in cancer' and 'Proteoglycans in cancer', were enriched in phase III, while 70 pathways were significant enriched at phase IV (P<0.05).…”
Section: Comprehensive Gene-pathway Analysismentioning
confidence: 99%
“…Chemokine (C-X-C motif) ligand 1 (CXCL1) secreted by tumor-associated lym-phatic endothelial cells induces integrin β1 to activate FAK/Akt signaling and promotes adhesion and metastasis of gastric cancer via MMP2/9 upregulation [121]. In HCC, IL-8 promotes invasive ability via the integrin β3-mediated PI3K/Akt pathway [122]. Gastrointestinal cancer is an inflammation-related disease.…”
Section: Integrinsmentioning
confidence: 99%
“…Taken together, the data support the critical roles of cancer cell adhesion molecules in tumor growth, metastasis, and chemoresistance ( Table 2). L-selectin Metastasis [113] Liver cancer E-selectin Tumor growth, Angiogenesis [111] Integrins Gastric cancer integrin β4 SOX2/HIF-1α signaling, EGFR EMT, Glucose metabolism, gefitinib chemoresistance [117,118] integrin β1 CXCL1, FAK/Akt signaling, MMP2/9 Adhesion, Metastasis [121] Pancreatic cancer integrin α3β1 ZIP4, ZEB1, STAT3 signaling, JNK signaling pathway Chemoresistance [119] Integrin family galectin-3, IL-8, NF-κB signaling Promote tumor growth, Metastasis [125] Colorectal cancer integrin α2β1 CDH17, FAK and Ras pathways Proliferation, Metastasis [120] integrin β1 TLR4, PI3K/Akt pathway Adhesion, Metastasis [123] Liver cancer integrin β3 IL-8, PI3K/Akt pathway Invasion [122] integrin αvβ3 galectin-1, FAK/PI3K/Akt signaling EMT, Sorafenib resistance [124] 3.4. Programmed Death-Ligand 1…”
Section: Integrinsmentioning
confidence: 99%